A Testable Theory of Imperfect Perception. (17th July 2014) - Caplin, Andrew; Martin, Daniel
<x xml:space="preserve">Abstract</x> We provide a characterisation of choice behaviour generated by a Bayesian expected utility maximiser. The observable signature of this standard model is the impossibility of raising utility by switching wholesale from one action to another. We provide applications to robustness, to the recovery of utility from choice data and to model classification.